2019
DOI: 10.1186/s42269-019-0059-0
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Toxoplasma gondii among a group of Egyptian patients with type I diabetes mellitus

Abstract: Background: Toxoplasmosis is probably one of the most common parasitic infections of humans. While infection of healthy adults is usually relatively mild, serious disease can result in utero or when the host is immunocompromised. Toxoplasmosis in diabetic patients may occur due to recently acquired acute infection or they may suffer from dissemination of reactivated latent infection. In the present study, the antinuclear antibody prevalence was tested to determine the possible relationship with Toxoplasma sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 36 publications
5
11
0
Order By: Relevance
“…(2019) reported other risk factors consisting of place of residence ( P < 0.001) and exposure to cats and soil ( P < 0.0001). [ 11 ] Accordingly, in the present study, we found a significant association between cat contact and the level of education in M2TD ( p -value<0.05) [ Figure 3 ].…”
Section: Discussionsupporting
confidence: 53%
“…(2019) reported other risk factors consisting of place of residence ( P < 0.001) and exposure to cats and soil ( P < 0.0001). [ 11 ] Accordingly, in the present study, we found a significant association between cat contact and the level of education in M2TD ( p -value<0.05) [ Figure 3 ].…”
Section: Discussionsupporting
confidence: 53%
“…When host immunity decreases in the state of T. gondii latent infection, latent infection is activated, causing severe acute toxoplasmosis again. In clinical studies, patients with solid malignant tumors, solid organ transplant (SOT) ( 26 ), human immunodeficiency virus (HIV)/AIDS, diabetes, and those receiving immunosuppressive agents have a high risk of reactivated toxoplasmosis ( 27 , 28 ). Therefore, reactivation of T. gondii infection is more common in patients with these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several seromolecular studies between T. gondii and DM [21,22,25,27,[36][37][38]. We previously performed a case-control serological investigation using ELISA test regarding such association, suggesting that 16/98 T1DM, 55/95 T2DM patients, and 16/94 control subjects had previous exposure to Toxoplasma.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, DM pathogenesis may be associated with infectious agents such as Helicobacter pylori [19] and Coxsackie B4 virus [20]. In this sense, T. gondii parasitic infection has been assumed to be involved in DM casualty, as demonstrated by seroprevalence data from Iraq, Egypt, Turkey, and Czech Republic [21][22][23][24][25][26][27]. In this case-control study, we shed light on the possible strain(s) of Toxoplasma isolated from diabetic patients referred to Imam Sajjad Hospital, Tehran, Iran, using nested-PCR and sequencing technologies.…”
Section: Introductionmentioning
confidence: 99%